Fatores abióticos relacionados à incidência e prevalência do fungo quitrídio na rã-das-corredeiras limnomedusa macroglossa - Ceccon, Emeline da Silva (2019)
Chytridiomycosis, an emerging infectious disease caused by the pathogenic fungus Batrachochytrium dendrobatidis (Bd), has been associated with population decline and extinction of amphibian species globally and is widely detected in the Atlantic Forest. Limnomedusa macroglossa is an anuran categorized as “critically endangered” in the state of Paraná. The present study evaluated potential associations between incidence and prevalence of the fungus chitride and temperature and relative humidity, and water temperature and pH, in a population of L. macroglossa in the state of Paraná. The fieldwork was carried out near the PR-484 highway, downstream of the Guarani River bridge, municipality of Três Barras do Paraná, from October / 2017 to September / 2018. The detection and quantification of Bd was performed by qPCR, from anuran skin secretion samples. 99 individuals were sampled, of which 34% were recaptured at least once. We confirmed the presence of Bd in the sampled population, with a prevalence of 17.4%. We detected a negativa association between temperature and prevalence and Bd load, and a positiva association between prevalence and load. The L. macroglossa population analyzed is more susceptible to infection and higher prevalence of Bd during winter. We suggest as a possible future study the identification of the existing Bd genetic line in order to determine effective conservation measures for L. macroglossa.